2022
DOI: 10.3389/fcimb.2022.817336
|View full text |Cite
|
Sign up to set email alerts
|

A Commensal Streptococcus Dysregulates the Pseudomonas aeruginosa Nitrosative Stress Response

Abstract: Chronic infections in the cystic fibrosis (CF) airway are composed of both pathogenic and commensal bacteria. However, chronic Pseudomonas aeruginosa infections are the leading cause of lung deterioration in individuals with CF. Interestingly, oral commensals can translocate to the CF lung and their presence is associated with improved lung function, presumably due to their ability to antagonize P. aeruginosa. We have previously shown that one commensal, Streptococcus parasanguinis, produces hydrogen peroxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…Prevotella is consistently the core bacteria of the respiratory tract [ 25 , 26 ]. Previous studies have demonstrated that commensal bacteria can interact with airway pathogens, such as Pseudomonas aeruginosa , to improve lung function and clinical stability [ 27 , 28 ]. As a result, we assumed that the specific airway microbiome composed of these commensal bacteria could inhibit MP and maintain lung environmental homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Prevotella is consistently the core bacteria of the respiratory tract [ 25 , 26 ]. Previous studies have demonstrated that commensal bacteria can interact with airway pathogens, such as Pseudomonas aeruginosa , to improve lung function and clinical stability [ 27 , 28 ]. As a result, we assumed that the specific airway microbiome composed of these commensal bacteria could inhibit MP and maintain lung environmental homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is the antagonism of CF pathogens by streptococci. Our laboratory has previously demonstrated that H 2 O 2 -producing streptococci, such as S. parasanguinis , can inhibit P. aeruginosa through the generation of RNI ( 18 , 20 ). Another possible mechanism is that these streptococci can modulate the host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrite can also react with H 2 O 2 to form reactive nitrogen intermediates (RNIs) that are antimicrobial. This commensal-generated RNI antagonism has been documented to inhibit oral pathogens as well as the CF pathogen Pseudomonas aeruginosa ( 18 , 35 , 36 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation